Nine Maternal Mortalities in 2 Weeks of Second COVID-19 Surge in Indonesia: A Case Series from One Large Tertiary Center - Wardhana, Manggala Pasca; Wulandari, Shabrina Avi; Rifdah, Salsabila Nabilah; Wafa, Ifan Ali; Sulistyono, Agus; Aditiawarman, Aditiawarman; Joewono, Hermanto Tri; Gumilar, Erry (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The fluctuating COVID-19 cases among the pregnant women’s population encountered increased of cases and maternal mortality. AIM: This research aimed to describe the case of maternal deaths caused by COVID-19. CASE REPORT: We present nine serial cases of maternal death caused by COVID-19 who were admitted to Dr. Soetomo General Academic Hospital for 14 days in June. We found 32 positive COVID-19 obstetric cases and reported nine maternal deaths with a fatality rate of up to 28%. Seven of nine patients had reverse transcription-polymerase chain reaction–confirmed SARS-CoV-2 infection, while two had a positive antigen swab. Half of the patients ≥35 years old, and five of nine patients had Class I obesity as preexisting comorbidity. This study reported the death of pregnant woman at their 2nd trimester and 3rd trimester presenting infected by severe COVID-19. The usual symptoms are dyspnea, cough, fever, and decreased consciousness. The result of chest X-ray examination among eight patients showed bilateral pneumonia. Most of cases were referrals from a secondary hospital due to overload hospital capacity. Three patients were directly transferred to the tertiary hospital without receiving initial treatment. Eight of 9 patients (88.9%) were transferred to intensive care unit and intubated due to low oxygen saturation. CONCLUSION: In conclusion, the limited hospital facility and lack of intensive care capacity for obstetric cases during the second wave of the COVID-19 pandemic may enhance the probability of mortality and morbidity in pregnant women infected by COVID-19.